Exploring the effect of leader other-oriented perfectionism on radical innovation - Wang, Le; Wang, Yu; Jin, Xiu (Frontiers in Psychology, 2025)
IntroductionRapid shifts in the global economy have increased the demand for innovation within companies, with radical innovation being a key factor for achieving competitive advantage, organizational success, and sustainable growth. Leadership traits can significantly affect employee behavior and attitudes, which in turn, can influence their work. leader’s others-oriented perfectionism, representing the interaction between a perfectionist leader and their employees, is particularly relevant in the workplace.MethodsThis study constructed a theoretical model to explore the relationship between leadership perfectionism and employee radical innovation and validated it through empirical research.ResultsThe findings indicate that there is a positive correlation between leader’s others-oriented perfectionism and employees’ work engagement, which in turn is related to radical innovation. In addition, there is a moderating effect of leader’s conscientiousness between the effects of perfectionism on employee work engagement. Employee promotion focus moderated the mediating role of work engagement in the relationship between leader perfectionism and employee radical innovation.DiscussionThe purpose of this study is to reveal the relationship between leadership perfectionism and employee work engagement and to explore how these findings can help organizations enhance employee breakthrough innovation. The findings will provide specific practical guidance for managers to encourage the combination of leadership perfectionism and accountability to drive employee work engagement and expand employee facilitation focus, ultimately impacting breakthrough innovation.